Analisis Hukum Islam terhadap Kerjasama Bagi Hasil Pengelolaan Lahan Perhutani Di Desa Kutorojo Pekalongan - Sasmito, Andi; Qomariyah, Siti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Perhutani's land management cooperation is unique because it uses three forms of cooperation at once in practice. So it is interesting to study whether this form of cooperation is in accordance with Islamic law. Therefore this study aims to find and understand the reasons for the practice of profit-sharing collaboration between Perhutani and the people of Kutorojo Village which use three forms of cooperation at once and how Islamic law analyzes these cooperative practices. This type of research is field research using a conceptual approach. The source of the data in this research is the results of interviews with the parties involved in the collaboration as well as Islamic legal concepts related to land management cooperation. The results of this study indicate that the three forms of cooperation carried out at the same time are in accordance with the needs in land management. The three forms of cooperation carried out are in accordance with the concept of cooperation in Islam because each form of cooperation has fulfilled its pillars and legal requirements.